Pengembangan Media Pembelajaran Berbasis Sparkol Videoscribe Tema Pertumbuhan si Hijau yang Berorientasi pada Literasi Sains Siswa SMP Kelas VII - Ilvi Triyani; Lukman Nulhakim; Liska Berlian (University of Bengkulu, 2022)
Sparkol Videoscribe based learning media is an intermediary in the learning process created by using the sparkol videoscribe application to convey learning materials to students in order to achieve a learning goal. This research aims to develop a sparkol videoscribe based learning media and determine the level of validity. The method used is research and development adapted from the development model according to Thiagarajan which consists of 3 stages: (1) Define; (2) Design; And (3) Development. The research instruments used in this study are interviews and validation sheets. The results of this study showed that the validity rate of sparkol videoscribe based on learning media the theme of the green growth oriented to science literacy, was obtained with an average score of 79.91% with a valid category. Based on the results of expert validation of the development of sparkol videoscribe based on learning media the theme of the green growth oriented to science literacy is valid for use in the learning process.